Answer:
y+ 3 = -1/3 (x-4)
Step-by-step explanation:
Simply plug in the values using (4, -3)
4 = x₁
-3 = y₁
Now one rule to keep in mind when plugging it in, since a negative and a negative make a positive, you have to add three instead of subtracting it.
19.6 would be the area of a single base circle πr² is the area formula
In order to keep the constant, the same and not vary there must be an indirect or inverse relationship to always maintain the value of k.
Thus both P and V are inversely related to each other.
Yes with any math expression or equation always use order of operation
First you open 2 parenthesis with x in each one:
(x )(x )=0
Then, you place the sign of the second term (the x term) in the first parenthesis.
(x+ )(x )=0
Next, you multiply the signs of the x term and the sign of the constant (the third term).
Since + × - = -, then you place a -.
(x+ )(x- )=0
You look at the constant (-18) and the second term (3). What two numbers multiplied give you -18 but subtracted (since the signs inside the parenthesis are opposite) give you 3? Those numbers are 6 and 3.
Since the result of the substraction need to be 3, you place the 6 with the + sign and the 3 with the negative sign (if you think of it, 6-3=3 but 3-6 = -3. That's the reason behind placing the numbers)
(x+6)(x-3)=0
Therefore,
x+6=0 or x-3=0
x=-6 or x=3
Your roots are -6 and 3.